Private Financing for Infrastructural Development: A Search for Determinants in Public–Private Partnerships in SSA: Array - Chikaza, Zakaria; Simatele, Munacinga (Acta Universitatis Danubius. Œconomica, 2021)
Understanding the determinants of Public-Private Partnerships remains a priority for policy makers in sub-Saharan Africa as leveraging on private sector resources and expertise to deliver public infrastructure projects is gaining appeal. However, due to uncertainty and ambiguity surrounding empirical approaches to private sector investments, public-private partnerships determinants in the region are still poorly understood. The study applies Extreme Bounds Analysis and Logit regressions to identify critical determinants of public-private partnerships using unbalanced panel data covering 40 sub-Saharan African countries from 1995 to 2020. Regression results identify five key variables (Regulatory Quality, Population, Gross Domestic Product, Foreign Direct Investment, and Government Spending) as positive significant determinants of infrastructure investments flows in sub-Saharan Africa. The implications of these results indicate ardent need for sub-Saharan African countries to promote prudent policies around these key drivers to promote private sector investments in the region.